Road Vehicle Automation 4 - Meyer, Gereon; Beiker, Sven.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is the fourth volume of the sub series of the Lecture Notes in Mobility dedicated to Road Vehicle Automation. lts chapters have been written by researchers, engineers and analysts from all around the globe. Topics covered include public sector activities, human factors and challenges, ethical, legal, energy and technology perspectives, vehicle systems development, as well as transportation infrastructure and planning. The book is based on the Automated Vehicles Symposium which took place in San Francisco, California (USA) in July 2016.
Public Sector Activities -- Human Factors and Challenges -- Ethics, Legal, Energy and Technology Perspectives -- Vehicle Systems and Technologies Development -- Transportation Infrastructure and Planning.
Keywords: Automotive engineering; Control engineering; Robotics; Automation; Artificial intelligence; Transportation engineering; Traffic engineering; Technological innovations; Automotive Engineering; Control, Robotics, Automation; Artificial Intelligence; Transportation Technology and Traffic Engineering; Innovation and Technology Management